Fighting an old battle in a new world : how IBFAN monitors the baby food market - Allain, Annelies; Nordberg, Olle; Mahler, Halfdan (The Dag Hammarskjold Foundation, 2005)
This publication focuses on the Baby Food Market and on breastfeeding. It provides an overview of the struggle of IBFAN to persuade governments and corporations to uphold international agreements.
Development dialogue, ISSN 0345-2328 2002, no. 2.
Keywords: politologie, politika, zdravotní politika; Marketing; mezinárodní agentury; zdraví dítěte; Infant Nutritional Physiological Phenomena; Child Health; Maternal Health; náhražky mateřského mléka; kojení; nutriční terapie, dietoterapie a výživa; zdraví matek; marketing; International Agencies; Infant Formula; Breast Feeding; ekonomie, ekonomika, ekonomika zdravotnictví; fyziologie výživy kojenců